ANALISIS TAX EFFORT, EFEKTIVITAS, KONTRIBUSI DAN PERTUMBUHAN PAJAK DAERAH KOTA BENGKULU TAHUN 2011-2014 - Dri Asmawanti; Novella Elvandari; Baihaqi Baihaqi (UNIB Press, 2016)
This study aimed to analyze the level of achievement of tax effort, effectiveness, contribution and tax growth of Bengkulu city in 2011-2014. The data used in this study are primary and secondary data obtained by taking the data and conduct interviews in DPPKA city of Bengkulu. This study uses aqualitative method. The object of this study is DPPKA city of Bengkulu. The test results showed that the attainment of tax effort, effectiveness, contribution and growth of Bengkulu city taxes that fluctuate.Key words: Tax Effort, Effectiveness, Contribution, Tax Growth